Use of direct oral anticoagulants in ICU patients. Part I – Applied pharmacology - Wahab, Abdul; Patnaik, Rupali; Gurjar, Mohan (Anestezjologia Intensywna Terapia, 2021)
Direct oral anticoagulants (DOACs) have revolutionized the field of anticoagulation in the last decade, mainly due to their fixed dosing, rapid onset of anticoagulant effect, and non-inferiority to vitamin K antagonists for both efficacy and safety. Also, the availability of specific and non-specific reversal agents makes these drugs popular. However, in critically ill patients, significant alterations in drug pharmacokinetics and pharmacodynamics might occur due to various ongoing pathophysiological derangements like decreased gastrointestinal absorption, increased volume of distribution, and impaired renal and/or hepatic function. Insight into these changes is essential regarding the safe and effective use of DOACs in critically ill patients. The current article is a narrative review on the use of DOACs in intensive care unit patients, covering ‘Applied pharmacology’; the second article in the series covers ‘Clinical evidence’.